Formulated Phospholipids as Non-Canonical TLR4 Agonists - Hong Liang; William R. Lykins; Emilie Seydoux; Jeffrey A. Guderian; Tony Phan; Christopher B. Fox; Mark T. Orr (MDPI AG, 2022)
Immunogenic agents known as adjuvants play a critical role in many vaccine formulations. Adjuvants often signal through Toll-like receptor (TLR) pathways, including formulations in licensed vaccines that target TLR4. While TLR4 is predominantly known for responding to lipopolysaccharide (LPS), a component of Gram-negative bacterial membranes, it has been shown to be a receptor for a number of molecular structures, including phospholipids. Therefore, phospholipid-based pharmaceutical formulations might have off-target effects by signaling through TLR4, confounding interpretation of pharmaceutical bioactivity. In this study we examined the individual components of a clinical stage oil-in-water vaccine adjuvant emulsion (referred to as a stable emulsion or SE) and their ability to signal through murine and human TLR4s. We found that the phospholipid 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) activated TLR4 and elicited many of the same immune phenotypes as canonical TLR4 agonists. This pathway was dependent on the saturation, size, and headgroup of the phospholipid. Interestingly, DMPC effects on human cells were evident but overall appeared less impactful than emulsion oil composition. Considering the prevalence of DMPC and other phospholipids used across the pharmaceutical space, these findings may contextualize off-target innate immune responses that could impact preclinical and clinical development.